Average direct cost of peripherally inserted central catheterization by nurses in hospitalized patients: a cost estimate - Maithê Gomes Lima Zandonadi; Danielly Negrão Guassú Nogueira; Amanda Salles Margatho do Nascimento; Paula Buck de Oliveira Ruiz; Natália Marciano de Araújo Ferreira; Suellen Karina de Oliveira Giroti; Flávia Meneguetti Pieri (Einstein (São Paulo))
ABSTRACT Objective: This study aimed to estimate the direct costs of peripherally inserted central catheterization by nurses for hospitalized patients. Methods: A cost estimation study using a quantitative approach was conducted in a public teaching hospital in northern Paraná to calculate the direct costs of peripherally inserted central catheterization. The population included all medical records of patients between 15 and 99 years of age who were hospitalized and underwent peripherally inserted central catheterization by nurses between January 1, 2019, and December 31, 2021, totaling 664 insertions. The sample comprised 631 insertions. Results: The catheter kits (epicutaneous catheter + introducer + angulators) corresponded to the items with the highest unit costs and the greatest impact on the composition of costs. The cost of peripherally inserted central catheterization was US$ 217.14 (SD=75.21), with the cost of materials and staff's labor being US$ 195.39 (SD=74.15) and US$ 20.00 (SD=2.22), respectively. Conclusion: Materials represented the highest cost, which was explained by the high unit cost of catheters and kits used in echocardiography, followed by the staff's labor costs. The estimated average direct cost allowed for financial visibility of the inputs used. The key challenge is promoting lasting changes in the behavior of managers who carry out administrative functions in healthcare institutions, where proper budget management directly affects the allocative efficiency of resources and the quality of care.